SAT0469 Calcinosis Cutis in Poly-Dermatomyositis: Clinical and Therapeutic Study. (9th June 2015) - Fredi, M.; Bartoli, F.; Cavazzana, I.; Carabellese, N.; Ceribelli, A.; Tincani, A.; Satoh, M.; Franceschini, F.
Abstract : Background: Subcutaneous or soft-tissue calcification is a recognized manifestation of many connective-tissue diseases; however, little is known about the pathogenesis and the treatment of this condition. Objectives: To identify the possible clinical and laboratory predictors of calcinosis by analyzing clinical and immunologic characteristic in a cohort of patients with a diagnosis of Poly-dermatomyositis (PDM). Methods: Seventy-four patients with a diagnosis of PDM referred to our Rheumatology and Immunology Unit were studied: 16 had calcinosis (C+) and 58 did not (C-). Clinical and laboratory data were collected from clinical charts. Statistical analysis was performed using the Chi-squared test and Student t test, p<0.05 is considered statistically significant. Results: The diagnoses in the C+ group were Dermatomyositis (12 patients), Polymyositis (1 patient) and Polymyositis and Systemic Sclerosis (SSc) Overlap syndrome (3 patients). The mean age at onset in the C+ group was 42.9 years (±20.4) and there was a predominance of females (81% vs 78%). Calcinosis occurred on average 43.7 months (SD 71.4 months) after diagnosis of connective-tissue disease. The first lesion was single in 11 cases (69%) and multiple in 5 (31%), with a predominant involvement of pelvic girdle (50%), root of higher limbs (25%), hands (25%), forearms and legs (13%). Pain associated to calcinosis was present in 9 cases (56%), while ulceration or superinfection of calcinosis were detected in 7 patients (44%). Therapies used for calcinosis were: colchicine (56%), diltiazem (44%), IVIg (44%), sodium thiosulfate cream (31%), calcium-channel blockers (19%), warfarin (13%), rituximab (13%), infliximab (13%). A limited improvement was reported: subjective improvement (colchicine, 1 case), reduction in pain (IVIg, 1) and resolution of rubor overlying calcifications (rituximab, 1). Surgical treatment of calcinosis was conducted in 38% of PDM patients. C+ group distinguishing features compared to C- group are shown in the table . Notably 4 out of 5 anti-PM/Scl (80%) as well as 4 out of 8 (50%) anti-MJ/NXP2 antibodies were found in patients with calcinosis. Conclusions: PDM patients with calcinosis constitute a disease subset characterized by: higher frequency of DM, inflammatory skin involvement as Gottron's papules, and increased frequency of pulmonary involvement (lower DLCO/VA) Anti-PM/Scl antibodies are more frequent in the C+ group (p<0.007): this reflects the increased frequency of Overlap PM-SSc Syndrome in C+ compared to C- (18.7% vs 9%). Anti-MJ/NXP-2 positivity tend to be more frequent in the C+ group (p=0.06). No drug treatment is effective in reducing the extension of calcinosis, but, in some cases, colchicine, intravenous Ig and rituximab induced a subjective improvement in symptoms related to calcinosis. Disclosure of Interest: None declared